Incidence and Persistence of High-risk Anogenital Human Papillomavirus Infection Among Female Youth With and Without Perinatally Acquired Human Immunodefiency Virus Infection: A 3-year Observational Cohort Study. (26th November 2019) - Phanuphak, Nittaya; Teeraananchai, Sirinya; Hansudewechakul, Rawiwan; Gatechompol, Sivaporn; Chokephaibulkit, Kulkanya; Dang, Hanh Le Dung; Tran, Dan Ngoc Hanh; Achalapong, Jullapong; Teeratakulpisarn, Nipat; Chalermchockcharoenkit, Amphan; Thamkhantho, Manopchai; Pankam, Tippawan; et al.
Abstract : Perinatally acquired HIV-infected female youth (PHIV) had an almost 2 times higher chance of having anogenital high-risk human papillomavirus (HR-HPV) incidence and persistence than Human Immunodeficiency Virus-uninfected youth. As HR-HPV persistence strongly predicts cancer development, PHIV should be urgently prioritized for HPV vaccination. Abstract: Background: Female youth with perinatally acquired human immunodeficiency virus (PHIV) may be at higher risk than uninfected youth for persistent anogenital human papillomavirus (HPV) infection, due to prolonged immunodeficiency. Methods: A 3-year cohort study was conducted between 2013 and 2017 among Thai and Vietnamese PHIV and HIV-uninfected females 12–24 years, matched by age group and number of lifetime sexual partners. For HPV genotyping, cervical and anal samples were obtained at baseline and annually. Vaginal samples were collected at baseline and every 6 months. Factors associated with high-risk HPV (HR-HPV) persistence and incidence were assessed. Results: We enrolled 93 PHIV and 99 HIV-uninfected females. Median age was 19 (interquartile range [IQR] 18–20) years. For the 7 HR-HPV types (16, 18, 31, 33, 45, 52, 58) in the nonavalent HPV vaccine, PHIV had significantly higher incidence ( P = .03) and persistence ( P = .01) than HIV-uninfected youth over a 3-year period. Having HIV (adjusted hazard ratio [aHR] 2.1, 95% confidence interval [CI] 1.1–3.9) and ever using illegal substances (aHR 4.8, 95% CI 1.8–13.0) were associated with incident 7 HR-HPV infections. HIV-positive status (adjusted prevalence ratio [aPR] 2.2, 95% CI 1.5–3.2), recent alcohol use (aPR 1.75, 95% CI 1.2–2.5), and higher number of lifetime partners (aPR 2.0, 95% CI 1.4–3.1, for 3–5 partners; aPR 1.93, 95% CI 1.2–3.2, for ≥6 partners) were significantly associated with persistent 7 HR-HPV infections. Conclusions: Female PHIV were at higher risk of having anogenital HR-HPV acquisition and persistence. Primary and secondary prevention programs for HPV infection and HPV-related diseases should be prioritized for PHIV children and youth.